Changes in the autumn precipitation and tropical cyclone activity over Central Vietnam and its East Sea - Wang, S.-Y. Simon; Promchote, Parichart; Truong, Luu Hong; Buckley, Brendan; Li, Rong; Gillies, Robert; Trung, Nguyen Tran Quoc; Guan, Biin; Minh, Ton That (Vietnam Journal of Earth Sciences, 2015)
Central Vietnam is particularly vulnerable to the impacts of climate change, with all of its incumbent socioeconomic and ecological consequences. This is due in part to the autumn timing of the peak rainfall season in Central Vietnam, at a time when tropical cyclones are most likely to make landfall. We conducted climate diagnostic analyses using meteorological and tropical cyclone data to understand the changing patterns of autumn rainfall and tropical cyclones, revealing an intensification of precipitation over Central Vietnam since the beginning of the 20th century that is associated with increased tropical cyclones in the adjacent sea. A warming of the sea surface temperature (SST) and enhanced southerly low-level winds are coincident with the above noted increase in rainfall and tropical cyclones. The underlying regional SST and circulation patterns are part of a hemispheric-scale change in the general circulation, i.e. a La Niña-like SST anomaly and a strengthened Walker circulation with the ascending branch located near Vietnam and far-western Pacific. We make the case with this paper that increasing autumn rainfall and tropical cyclones should be taken into account any mitigation and adaptation plans anticipated for Central Vietnam. References An, S.-I., J.-W. Kim, S.-H. Im, B.-M. Kim, and J.-H. Park, 2012: Recent and future sea surface temperature trends in tropical Pacific warm pool and cold tongue regions, Clim. Dynamics, 39(6), 1373-1383. Buckley, B. M., R. Fletcher, S.-Y. S. Wang, B. Zottoli, and C. Pottier, 2014: Monsoon extremes and society over the past millennium on mainland Southeast Asia, Quaternary Science Reviews, 95(0), 1-19. Chang, C., P. A. Harr, and H.-J. Chen, 2005: Synoptic disturbances over the equatorial South China Sea and western Maritime Continent during boreal winter, Mon. Wea. Rev., 133(3), 489-503. Chen, J., R. Wu, and Z. Wen, 2012: Contribution of South China Sea tropical cyclones to an increase in southern China summer rainfall around 1993, Advances in Atmospheric Sciences, 29, 585-598. Chen, M., P. Xie, J. E. Janowiak, and P. A. Arkin, 2002: Global Land Precipitation: A 50-yr Monthly Analysis Based on Gauge Observations, Journal of Hydrometeorology, 3(3), 249-266. Chen, Y., and D. Tang, 2012: Eddy-feature phytoplankton bloom induced by a tropical cyclone in the South China Sea, International Journal of Remote Sensing, 33(23), 7444-7457. Compo, G. P., J. S. Whitaker, P. D. Sardeshmukh, N. Matsui, R. J. Allan, X. Yin, B. E. Gleason, R. S. Vose, and E. al., 2011: The Twentieth Century Reanalysis Project, Q. J. Roy. Meteor. Soc., 137, 1-28. Koetse, M. J., and P. Rietveld, 2009: The impact of climate change and weather on transport: An overview of empirical findings, Transportation Research Part D: Transport and Environment, 14(3), 205-221. L’Heureux, M. L., S. Lee, and B. Lyon, 2013: Recent multidecadal strengthening of the Walker circulation across the tropical Pacific, Nature Clim. Change, 3(6), 571-576. McElwee, P. D., 2012: Payments for environmental services as neoliberal market-based forest conservation in Vietnam: Panacea or problem?, Geoforum, 43(3), 412-426. Murakami, H., B. Wang, and A. Kitoh, 2011: Future Change of Western North Pacific Typhoons: Projections by a 20km Mesh Global Atmospheric Model*, J. Climate, 24(4), 1154-1169. Neil Adger, W., 1999: Social vulnerability to climate change and extremes in coastal Vietnam, World Development, 27(2), 249-269. Smith, T. M., R. W. Reynolds, T. C. Peterson, and J. Lawrimore, 2008: Improvements to NOAA’s Historical Merged Land–Ocean Surface Temperature Analysis (1880-2006), J. Climate, 21(10), 2283-2296. Tu, J.-Y., C. Chou, and P.-S. Chu, 2009: The abrupt shift of typhoon activity in the vicinity of Taiwan and its association with western North Pacific-East Asian climate change, J. Climate, 22(13), 3617-3628. Tung, K.-K., and J. Zhou, 2010: The Pacific’s response to surface heating in 130 yr of SST: La Niña-like or El Niño-like?, J. Atmos. Sci., 67(8), 2649-2657. Wang, S.-Y., and A. J. Clark, 2010: Quasi-decadal spectral peaks of tropical western Pacific SSTs as a precursor for tropical cyclone threat, Geophys. Res. Lett., 37(21), L21810. WorldBank, 2001: WWF Indochina Program, edited by W. Bank, http://mabvietnam.net/WWF Indochina Programme.htm. Yang, L., Y. Du, S. Xie, and D. Wang, 2012: An interdecadal change of tropical cyclone activity in the South China Sea in the early 1990s, Chinese Journal of Oceanology and Limnology, 30, 953-959. Yen, M.-C., T.-C. Chen, H.-L. Hu, R.-Y. Tzeng, D. T. DINH, T. T. T. NGUYEN, and C. J. Wong, 2011: Interannual variation of the fall rainfall in Central Vietnam, J. Meteor. Soc. Japan (気象集誌). 第 2 輯, 89, 259-270. Yokoi, S., and J. Matsumoto, 2008: Collaborative effects of cold surge and tropical depression-type disturbance on heavy rainfall in central Vietnam, Mon. Wea. Rev., 136(9), 3275-3287. Yuen, B. K. P., and A. Kumssa, 2010: Climate Change and Sustainable Urban Development in Africa and Asia, Springer, 262 pp.